A Norse Farmstead in the Outer Hebrides Excavations at Mound 3, Bornais, South Uist - Sharples, Niall (Oxbow Books, 2005)
This volume examines South Uist, a small island in the soutern half of the Outer Hebrides. In the middle of the island lies the township of Bornais. This covers a particularly flat area of land which means that the three mounds can be seen all the more clearly. These mounds have been identified as being from the Viking period, with evidence of pre-Viking habitation at the site coming from Iron Age sherds. The excavation of the Bornais settlement is a long-term project, which has been going since 1994. This first volume of results of the excavation focuses on Mound 3, but includes a discussion of the topographic and geophysical survey of all the mounds. There is also considerable analysis of the environmental remains and radiocarbon dating.